STUDENTS’ ATTITUDES IN ENGLISH CLASSROOM AT MAN 2 MODEL MEDAN - Sarah Hendratno Simanjuntak; Najwa Kamila Harpan (Adisam Publisher, 2026)
This study explores the complex attitudinal profile of Grade X students at MAN 2 Model Medan toward English classroom interaction and examines how these attitudes reflect in their classroom participation. Operating within a descriptive qualitative design, the study utilized an open-ended questionnaire distributed to ten participants to capture their cognitive, affective, and behavioral dimensions. The findings reveal a dualistic psychological pattern where students demonstrate high cognitive appreciation for the utility of verbal interaction, yet this is often obstructed by significant affective barriers, specifically communication apprehension and fear of negative peer evaluation. These internal states directly dictate participation patterns on the classroom continuum, with resilient students manifesting active engagement and anxious students defaulting to defensive silence. The results imply that traditional pedagogical encouragement is insufficient to induce verbal participation when underlying affective barriers remain unaddressed. Therefore, it is suggested that English teachers minimize stressful teacher-fronted elicitation and prioritize the creation of low-anxiety, collaborative learning environments. These findings provide critical insights for EFL educators in Islamic secondary schools seeking to bridge the gap between learner cognition and active communicative performance.